The geometry of a synaptic intermediate in a pathway of bacteriophage lambda site-specific recombination. - Cassell, G (1999)
Bacteriophage lambda uses site-specific recombination to move its DNA into and out of the Escherichia coli genome. The recombination event is mediated by the phage-encoded integrase (Int) at short DNA sequences known as attachment ( att ) sites. Int catalyzes recombination via at least four distinct pathways, distinguishable by their requirements for accessory proteins and by the sequence of their substrates. The simplest recombination reaction catalyzed by Int does not require any accessory proteins and takes place between two attL sites. This reaction proceeds through an intermediate known as the straight-L bimolecular complex (SL-BMC), a stable complex which contains two attL sites synapsed by Int. We have investigated the orientation of the two substrates in the SL-BMC with respect to each other using two independent direct methods, a ligation assay and visualization by atomic force microscopy (AFM). Both show that the two DNA substrates in the complex are arranged in a tetrahedral or nearly square planar alignment skewed towards parallel. The DNA molecules in the complex are bent.